Juveniles as victims of criminal acts committed under the misuse of computer network - Spasojević Đorđe; Miladinović-Bogavac Živanka (Trendovi u Poslovanju)
The fact is that technological development has improved many aspects of life, but at the same time, according to the principle of a double-edged sword, it created justifiable fear in view of the numerous negative consequences of its misuse. A special segment of technological development where such misuses are increasingly present are computer networks. Such fear is further expressed when it comes to juveniles, who, due to the characteristics of this development period, represent easy targets, which often leads to serious and long-term consequences. Although this category of people, as a rule, works well with such innovations, their inexperience can easily put them in danger. For the above reasons, this problem should be approached from a theoretical point of view. It seems that questions that have been discussed in this paper deserve special attention: the impact of internet dependency on victimization; typology of juvenile victims; characteristics of victims of internet pedophilia. The use of meta-analysis has resulted in the synthesis of the results of existing research and attitudes, which served as a basis for a critical review and an attempt to give a modest contribution to solving these issues.